(untitled) (AYUSHDHARA, 2019)
Hair disorders are a common complaint in today’s era and can be caused by a number of conditions. The ultimate aim of the study is to provide a guide for evaluating hair disorders commonly occurring in our environment. A prospective observational study was conducted from January 2018 to December 2018. Patient suffering from hair disorders of all age groups were included in the study. A prevalence study of 241 newly diagnosed cases of various hair and scalp disorders have been reported. The objective of the study is to review the prevalence of hair disorders in Assam for early diagnosis and to prevent complications. The most common disorder according to our study is Indralupta. Also it has been seen that many of the patients were suffering from Mandagni Dusti. For research and development in the field of trichology, this area bears potential and scope. It is important to note that as more number of hair related cases visit Government Ayurvedic College, it reflects that patients are getting satisfactory improvement with Ayurvedic modalities in hair and scalp related disorders.